CORPORATE GOVERNANCE, AUDIT QUALITY, AND EARNINGS MANAGEMENT: THE MODERATING ROLE OF INDUSTRIAL CLASSIFICATION ON IDX-LISTED COMPANIES - Anastasia, Regina (Stability: Journal of Management and Business, 2024)
Earnings management practices carried out by companies are still a concern, especially in corporate governance and audit quality of public companies. This study aims to see the correlation between corporate governance and audit quality on earnings management of companies listed on the Indonesia Stock Exchange during the 2021-2021 period. In addition, this study also examines the role of the type of company industry as a moderating variable of the relationship between governance and audit quality with corporate earnings management. The sample in this study was all companies that are part of the energy, infrastructures, transportation logistics, healthcare, and technology industries, with a total of 618 samples. The results of the moderated regression analysis show that industry type significantly affects the relationship between board size and audit quality with earnings management practices. These results indicate that governance mechanisms in each type of industry are still different and provide insight to regulators to consider governance standards specifically for each industry.